Ginsenoside Rg1 Improves Inflammation and Autophagy of the Pancreas and Spleen in Streptozotocin-Induced Type 1 Diabetic Mice - Yi Zong; Weihua Yu; Hanghang Hong; Zhiqiang Zhu; Wenbo Xiao; Kewu Wang; Guoqiang Xu (International Journal of Endocrinology)
Background. Ginsenoside Rg1 (Rg1) is one of the key bioactive components of the precious Traditional Chinese Medicine that has been used to treat diabetes in China. Ginsenosides have been reported to protect diabetics from tissue damage, inflammation, and insulin resistance. Type 1 diabetes (T1D) is an organ-specific autoimmune disease that occurred frequently among adolescents over the world, its development was related to inflammation and β-cells immunodeficiency. The aim of this study is to explore the biological mechanism of Rg1 on inflammation and autophagy of β-cells in T1D and its therapeutic potential. Methods. The model of T1D mice was established by injecting Streptozotocin (STZ) (55 mg/kg) or citric acids once a day for 5 days and from the fourth day of injection, mice were administered with Rg1 (20 mg/kg) or saline by gavage once a day for 12 days. Hematoxylin-eosin staining, immunofluorescence, ELISA, quantitative real-time PCR, and Western blot were used to observe the histopathological changes, inflammatory factor levels, and autophagy markers after administration of ginsenoside Rg1. Results. Compared to the T1D mice, Rg1 improved the weight (p<0.05) and blood glucose (p<0.01) of mice, advanced the injury and apoptosis of β-cells in islets (p<0.01), and markedly inhibited the protein expression degrees of CD45, CXCL16, ox-LDL, and TF in the pancreas and spleens (p<0.01), also activated the degrees of insulin in serum (p<0.01). Besides, in T1D mice’ pancreas and spleen, Rg1 markedly repressed the IL-1β, TNF-α, and NOS2 mRNA levels (p<0.05 or p<0.01), inhibited the CXCL16, NF-κB, and TF proteins (p<0.05 or p<0.01), while elevating the ratio of LC3 II/I (p<0.01) and P62 (p<0.05) protein level. Conclusions. This study proved that Rg1 protected mice against T1D possibly by improving islet injury and tissue inflammation, raising serum insulin, and tissue autophagy marker.